Parameterization of ionospheric height variations by antenna pattern synthesis technique - Rhazali Z.A.; Zain A.F.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper introduces a new alternative in representing temporal ionospheric height of peak electron density, hmax, variations using array antenna parameters. The use of polar cyclic diagram based on antenna radiation pattern is proposed. The height variations are illustrated using arrays of two-element arrays with array spacing in the x-direction of ? /8, and phase of ? /3, and with element spacing in the y-direction of ? /4, and phase of zero. The antenna equivalent model of peak height variations may complement the classical way of representing hmaxtemporal variations and acts as a signature to any ionospheric height of peak density variations. It constitutes the novelty of the study. © 2014 IEEE.